RESEARCHES ON ECONOMIC POTENTIAL OF AGRICULTURAL TOURISM IN WESTERN ROMANIA - Marius BOIȚǍ; Gheorghe PRIBEANU; Ionela Mihaela MILUTIN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Agricultural tourism, any other sphere of the science of tourism activity is subordinated both to the environment and food reserves, being its “raw material", its scope and activity. This study seeks to identify and assess the potential of bio-resources and of bio-productivity in order to develop rural tourism; for the completion of modern indicators of territorial capital; development of eco-bio tourism packages in Western Romania. Our research has focused on identifying the traditional bio-resources and developing a strategy for promoting and implementing in rural tourism, on the identification and evaluation of bio-productivity in order to develop rural tourism in Western Romania. Through this study, we were able to capture current and future main sides of the agricultural tourism in a territorial system.